Fracturing Fluid Optimization in Limestone Formation Using Guar Gum Crosslinked Fluid - Swadesi, Boni; Ilyas, Ahmad Azhar; Kristiati, Maria Theresia; Asmorowati, Dewi; Sobri, Ahmad; Bayu, Sukma; Azwar, Malvin Larasyad (Journal of Earth Energy Engineering, 2023)
The design of the fracturing fluid is a very important aspect of the success of hydraulic fracturing. The most common fracturing fluid used in hydraulic fracturing is the cross-linked guar gum fracturing fluid. To determine the optimal fracturing fluid concentration, it is necessary to analyze the fracturing fluid optimization to obtain the best fracturing results in terms of fracturing fluid rheology, regain permeability, hydraulics, cost, fracture geometry, and FOI. From this analysis, it is expected to obtain the most optimal fracturing fluid to be applied to the JARWO Well. This research was conducted by conducting a sensitivity test method for selecting the concentration of the fracturing fluid system that affects the fracture fluid rheology, regain permeability, fracturing fluid hydraulics during injection, total material cost, fracture geometry, and the resulting FOI. The sensitivity of the fracturing fluid concentration that was tested was the system concentration of 35 pptg, 40 pptg, and 45 pptg. Each fracturing fluid is tested in the laboratory to obtain rheology which will then be simulated using MFrac software to obtain the fracture geometry formed. The results of the analysis of the concentration of each fracturing fluid showed that the fracturing fluid with a system concentration of 40 pptg was the most stable in viscosity at pumping time to produce the highest FOI. The hydraulic fracturing fluid with a concentration of 40 pptg is better than that of a concentration of 45 pptg. From the performance of regaining permeability and residue, it is quite good when compared to fracturing fluid with concentration of 45 pptg, and the cost is lower when compared to a fracturing fluid with concentration of 45 pptg. So that the fracturing fluid with a system concentration of 40 pptg is the most optimal fluid for use in hydraulic fracturing activities at the JARWO Well.